Systematic review of the epidemiology of a single physical trauma and cancer. (July 2021) - McElvenny, Damien M; Davis, Alice; Dixon, Ken; Alexander, Carla; Gupta, Girish; Nixon, Ioanna; Crawford, Joanne O
Background: A systematic review of single physical trauma and cancer was carried out, with a meta-analysis where deemed appropriate. Methods: A comprehensive search of the literature including databases such as Medline and Embase identified 1529 potentially relevant papers for inclusion. A further 89 potentially relevant studies were identified from bibliographies. After review of titles and abstracts and then full papers, a total of 77 studies were included in the broader review of trauma and cancer, and 31 of these studies considered single physical trauma and cancer. The searches were carried out in June 2016. Results: Although physical trauma as a cause of cancer has been an issue of clinical interest for decades, the epidemiological evidence was sparse. Only for traumatic brain injury and brain cancer was there considered a sufficient number of epidemiological studies for a meta-analysis. A random effects meta-relative risk for glioma from cohort studies was 0.96 (95% CI: 0.49 to 1.88) and 1.53 (95% CI: 1.02 to 2.27) for case-control studies. The equivalent results for meningioma were 1.22 (95% CI: 0.85 to 1.76) and 1.88 (95% CI: 0.84 to 1.49) respectively. Conclusions: Further work is required to clarify whether physical trauma has a role in cancer development, perhaps by exploiting trauma registries.